2009
DOI: 10.5585/exacta.v6i2.1010
|View full text |Cite
|
Sign up to set email alerts
|

Troca Rápida de Ferramentas: estudo de casos em diferentes segmentos industriais

Abstract: Este artigo propõe uma análise e aprofundamento do atual estado da arte no que diz respeito aos tempos de preparação de máquinas, uma vez que este é um importante aspecto de ganho de competitividade e melhoria de desempenho organizacional. Por meio da condução de um levantamento bibliográfico, relacionaram-se os principais aspectos relevantes ao tema, destacando-se variações de metodologias e métodos de implementação surgidos nas últimas décadas. Com o intuito de verificar o grau de aplicação desses conceitos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
8

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 7 publications
0
6
0
8
Order By: Relevance
“…Getting tools and fixtures ready: The work team leader must know the number of the part that is going to be programmed as well as get the corresponding tools and coil ready so that the operator can continue with their activities and not lose time. 15 25 30 10 25.0%…”
Section: Internal External Internal Externalmentioning
confidence: 99%
See 1 more Smart Citation
“…Getting tools and fixtures ready: The work team leader must know the number of the part that is going to be programmed as well as get the corresponding tools and coil ready so that the operator can continue with their activities and not lose time. 15 25 30 10 25.0%…”
Section: Internal External Internal Externalmentioning
confidence: 99%
“…Despite the fact that SMED is nothing new, few studies on the application of it are available and those that are have had the exchange of ideas as their focus [12][13][14][15]. For this reason, the objective of this document is to present the implementation of a pilot SMED process that was carried out in a metalworking factory in the city of Bucaramanga, Santander, Colombia during 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of research on SMED have been widely described and presented with the exchange of Dies as the main focus (Monden 1984;Johansen and McGuire 1986;Sepheri 1987;Quinlan 1987;Noaker 1991;Gilmore and Smith 1996;McIntosh et al 2000;Fogliatto and Fagundes 2003;Satolo and Calarge 2008). Van Goubergen and Van Landeghem (2002) analyzed how equipment design can improve existing setup times.…”
Section: Single-minute Exchange Of Diementioning
confidence: 99%
“…This perspective is also supported by Hicks (2007) from a information management perspective and by Pardi (2005) from a socioeconomic perspective. Satolo and Calarge (2008) analyzed the applicability of the SMED methodology and concluded that there are large differences among the firms that implemented it. More importantly, the differences were based on organizational barriers, resistance to change and difficulties in identifying opportunities for improvement.…”
Section: The Operationalization Of Smedmentioning
confidence: 99%
See 1 more Smart Citation